2016
DOI: 10.1186/s41065-016-0010-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of Mount Huang honey bee (Apis cerana) populations: evidence from microsatellite polymorphism

Abstract: BackgroundThe Mount Huang eastern honey bees (Apis cerana) are an endemic population, which is well adapted to the local agricultural and ecological environment. In this study, the genetic structure of seven eastern honey bees (A. cerana) populations from Mount Huang in China were analyzed by SSR (simple sequence repeat) markers.ResultsThe results revealed that 16 pairs of primers used amplified a total of 143 alleles. The number of alleles per locus ranged from 6 to 13, with a mean value of 8.94 alleles per l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Under the complex ecological conditions in China, Chinese honeybees are well adapted to flowering plants and climatic variation in different regions, thus playing an irreplaceable and extremely important ecological role relative to that of exotic bees (Zhou et al, 2021;Chen and Luo, 2023). Research has shown that even Chinese honeybee populations in limited geographic areas may have great genetic differences, resulting in high diversity and providing a material foundation for the development and utilization of Chinese honeybee genetic resources (Yin and Ji, 2013;Liu et al, 2016;Yu et al, 2019;Cao et al, 2021;Fang et al, 2022). Changes in the climate and environment, industrialization, pesticide implementation, and other factors have affected honeybee resources.…”
Section: Introductionmentioning
confidence: 99%
“…Under the complex ecological conditions in China, Chinese honeybees are well adapted to flowering plants and climatic variation in different regions, thus playing an irreplaceable and extremely important ecological role relative to that of exotic bees (Zhou et al, 2021;Chen and Luo, 2023). Research has shown that even Chinese honeybee populations in limited geographic areas may have great genetic differences, resulting in high diversity and providing a material foundation for the development and utilization of Chinese honeybee genetic resources (Yin and Ji, 2013;Liu et al, 2016;Yu et al, 2019;Cao et al, 2021;Fang et al, 2022). Changes in the climate and environment, industrialization, pesticide implementation, and other factors have affected honeybee resources.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Sheppard and Meixner [7] consider the honeybee subspecies Apis mellifera pomonella to be endemic to Kazakhstan. This subspecies is believed the result of the crossbreeding between Apis mellifera and Apis cerana [8].…”
Section: Introductionmentioning
confidence: 99%
“…Many molecular markers such as restriction fragment length polymorphism (RFLP), random amplified polymorphic DNA (RAPD) and mitochondrial DNA (mtDNA) analyses have been used in honey bee population genetics studies, but for the last 20 years, microsatellite loci have been quite widely used due to their features such as high polymorphism, multiallelicity, abundance in the genome and easy scorable (Kandemir & Kence, 1995;Smith et al, 1997;Bodur et al, 2007;Kekeçoğlu et al, 2009;Özdil et al, 2009;Liu et al, 2016;Rahimi et al, 2016;Haddad et al, 2018;Hassett et al, 2018;Yu et al, 2019;Özdil et al, 2022). Latterly, single nucleotide polymorphisms (SNPs) have been used in population genetics studies, however, thanks to the advantages provided by microsatellites, they could not get ahead of microsatellites even in the genomic era (Zimmerman et al, 2020;Mukherjee et al, 2022;Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%